Theoretical Study of Isolated Attosecond Pulse Generation with Two Methods (Journal of Atomic and Molecular Sciences, 2016)
We theoretically investigated high-order harmonic generation and isolatedattosecond pulse generation from a model of helium atom by two methods: numericallysolve time dependent Schrödinger equation (TDSE) by splitting-operator methodand Lewenstein's strong field approximation theory. A left circularly polarized pulse(800 nm) is combined to a right circular polarized pulse (1200 nm) with a time delay of4 fs. A supercontinuum spectrum plateau with a broad bandwidth of 215 eV (from 230to 445 eV) is obtained for the case of $I_0=7×1014W/cm².$ By superposing a bandwidthof 70 eV in the plateau region, an linear polarized isolated attosecond pulse with theduration of about 56 as can be obtained. Moreover, we illustrate the quantum pathcontrol in terms of the time-frequency analysis by Morlet wavelet transform method.